Policies to address the challenges of existing and new forms of informality in Latin America - Abramo, Lais (United Nations, ECLAC, 2022)
The phenomenon of informality in Latin America is strongly conditioned by the main structural axes of the social inequality matrix. It is a heterogeneous and multifaceted phenomenon in which socioeconomic, territorial, gender, age and ethnic/racial inequalities are manifested. Deeper analysis of the characteristics and nature of this phenomenon, taking into account that diversity and heterogeneity, is a still pending task that calls for the production of data and information systems able to encompass those various dimensions. This is also a central condition for the design and implementation of policies capable of tackling informality in a more appropriate, efficient and sustainable manner and of making progress in expanding the possibilities for better-quality and more protected productive and labour market insertion, as well as in closing gaps in access to decent work. This paper reviews the conceptual discussion on existing and new forms of informality in Latin America and analyses in depth the relationship between informality and the various axes of inequality that shape its labour markets, with an emphasis on the territorial and subnational dimension. Likewise, based on that diagnostic assessment, policy recommendations are proposed to advance towards the formalization of informality in its existing and new forms. Summary .– Introduction .– I. Existing and new forms of informality and new atypical forms of employment in Latin America .– II. Informality and the social inequality matrix in Latin America: territory, gender, youth and ethnicity and race .– III. Policies for formalizing informality in its existing and new forms:experiences and challenges.
11362/47774
Keywords: Graue Literatur; employment; inequality; social policies and programmes; social rights employment; informal sector; labour market; equality; social aspects; gender equality; youth; ethnic and racial groups; employment policy; EMPLEO; SECTOR INFORMAL; MERCADO DE TRABAJO; IGUALDAD; ASPECTOS SOCIALES; IGUALDAD DE GENERO; JUVENTUD; GRUPOS ETNICOS Y RACIALES; POLITICA DE EMPLEO; EMPLOYMENT; INFORMAL SECTOR; LABOUR MARKET; EQUALITY; SOCIAL ASPECTS; GENDER EQUALITY; YOUTH; ETHNIC AND RACIAL GROUPS; EMPLOYMENT POLICY